The availability of dimensions of creative leadership among secondary school principals in Wadi Al-Dawasir and its relationship to institutional excellence from the teachers’ point of view - Al-Dossary, Mitab Fahad Matruk (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the availability of dimensions of creative leadership among secondary school principals in Wadi Al-Dawasir and its relationship to institutional excellence from the teachers’ point of view. In Wadi Al-Dawasir Governorate, Kingdom of Saudi Arabia, and the results of the study concluded: that the degree of creative leadership practice among secondary school principals in Wadi Al-Dawasir from the teachers’ point of view, its arithmetic mean was (4.11) with a degree of appreciation (great), and at the level of sub-domains: sensitivity to problems got the highest Average (4.14), flexibility (4.13), third: perseverance (4.13), fourth: originality (4.10), and finally initiative (4.08), all with a grade (high). The results also showed that the level of institutional excellence in secondary schools in Wadi Al-Dawasir from the point of view of teachers, Its arithmetic mean was (4.06) with a degree of appreciation (great), and the results showed that there were no statistically significant differences at the level (0.05 ≥ α) between the average estimates of the study sample due to the two variables (educational qualification, specialization), while There were differences attributed to the variable (years of service) in favor of the category of 10 years or more, and the correlation relationship reached (0.85) and reflects a strong relationship of creative leadership to institutional excellence.